HISTORIOGRAPHIC METAFICTION AND MAGICAL REALISM IN WINTERSON’S THE PASSION AND MORRISON’S BELOVED - Nazila Heidarzadegan; Dulfqar M. Abdulrazzaq (Universitas Islam Sumatera Utara (UISU), 2022)
This paper aims to explore the role of Historiographic Metafiction and Magical Realism in the enrichment of the plot of Jeanette Winterson’s The Passion and Toni Morrison’s Beloved, clarifying the concept of Magical Realism, its goals, and the reasons for its emergence and importance in literature. Both novels are a distinctive model of Historiographic Metafiction, and both authors have reversed all norms and traditions that are imposed by religious beliefs and patriarchal society to modulate the historical facts and present the familiar and common facts in a different form, and women are no longer oppressed as once their presence were intentionally obliviated in history. They have also mingled fiction with reality, creatively. Winterson embodies Magical Realism's elements innovatively, as she constructed a fictitious and mythical world, creating mythical creatures that are difficult to imagine or explain, whereas Morrison presents slavery different from what is common, portraying the pains of slavery via mixing fiction and reality, to make ordinary become unusual and familiar seem unfamiliar.